Ghanaian Siblings' Experiences of a Brother or Sister with a Mental Disability - Cooper, Amanda (The Chicago School of Professional Psychology, 2017)
The following study explored the experiences of Ghanaian adult siblings of a brother or sister with a mental disability in Accra, Ghana. The literature review included international and multidisciplinary research on culture, Ghana, Ghanaian culture, family caregiver experiences, and adult siblings of individuals with a mental disability. A descriptive phenomenological design was employed to capture and describe the essence of the experiences of the participants of this study. The primary research question explored through this design was: what is the experience of being an adult sibling of a brother or sister with a mental disability in Ghana? The secondary research question was: what are the factors that impact the adult caregiver in caring for the sibling with a mental disability in Ghana? A purposeful sampling method was used to recruit 15 adult siblings of an individual with a mental disability with the assistance of a school for individuals with special needs located in Accra, Ghana. Semi-structured interviews were used to collect the data for this study. Five themes were identified in relation to the primary research question: 1) impact on self, 2) sibling relationship, 3) family, 4) interactions with society, and 5) caregiver. In answer to the secondary research question, several factors were found to impact the adult siblings in caring for their brother or sister: level of care needed, total number of siblings, sibling rank order, age, gender, parents living or passed, parental status, and financial status. The results of the study were discussed in relation to the reviewed literature, implications for the findings, and recommendations for future research were included. This study added to existing body of international psychology literature, demonstrated the importance of attending to the influence of culture when seeking to understand the experiences and needs of adult siblings of a brother or sister with a mental disability, and has the potential to inform systems of support for Ghanaian siblings of individuals with mental disabilities.